Determinants of Economic Inequality Among Provinces in Sumatera Island - Sitompul, Gabriel Amadeus; Syafii, M. (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This study aims to analyze the effect of Government Expenditure, Infrastructure, Total Working Age Population, and Domestic Investment on the Economic Inequality between provinces on Sumatra Island from 2012-2022. The analytical method used in this study is the Panel Data Regression method. The data type used is secondary data for 11 years (2012-2022) sourced from the Central Indonesia Statistic Agency, which is processed with the Eviews program. The study results show that Domestic Investment variables have a positive and significant effect on the Economic Inequality between provinces on Sumatra Island in 2012-2022. Meanwhile, the Infrastructure, Government Expenditure, and Total Working Age Population variables negatively and significantly affected the Economic Inequality between provinces on Sumatra Island from 2012-2022.